Multicenter Study of Utility and Acceptability of Depression and Anxiety Screening in Adolescents and Young Adults With Childhood‐Onset Systemic Lupus. Issue 4 (23rd December 2022) - Rubinstein, Tamar B.; Dionizovik‐Dimanovski, Marija; Davis, Alaina M.; Smith, Chelsey; Faust, Lauren; Rutstein, Beth; Mitchell, Manda; Jones, Jordan T.; Harris, Julia G.; Rodriguez, Martha; Tesher, Melissa; Onel, Karen; et al.
Abstract : Objective: To determine the utility and acceptability for depression and anxiety screening of adolescents and young adults (AYA) with childhood‐onset systemic lupus erythematosus (cSLE) in the pediatric rheumatology setting. Methods: AYA with cSLE, ages 12–21 years, from 8 collaborating sites, were consecutively screened for depression and anxiety with the Patient Health Questionnaire‐9 (PHQ‐9) and Generalized Anxiety Disorder 7‐item scale (GAD‐7). Demographic and disease characteristics were collected, as well as patient‐reported outcome measures using the Patient Reported Outcomes Measurement Information System (PROMIS) pediatric profile‐25. Acceptability of screening was assessed with postscreening surveys completed by AYA and parents. Chi‐square and Wilcoxon rank sum tests examined the relationship between patient characteristics and history of previous screening. Spearman correlations examined relationships between screening scores, PROMIS domains, and other disease factors. Results: Among 106 AYA screened, 64 (60%) had been previously screened, 25 (24%) by general pediatricians. Thirty‐two (30%) AYA screened positive, including 24% for depression, 17% for anxiety, and 14% for suicidal ideation. Depression and anxiety symptom severity were highly correlated with increased PROMIS domain scores for fatigue and pain interference and moderately correlated with increased pain severity, decreased mobility, and decreased peer relationships. Eighty‐six percent of AYA and 95% of parents expressed comfort with screening in the pediatric rheumatology setting. Conclusion: Depression, anxiety, and suicidal ideation are common among AYA with cSLE, and symptoms are correlated with important patient‐reported outcomes. Mental health screening in the pediatric rheumatology setting was highly acceptable among AYA with cSLE and their parents.